A bidirectional tuned liquid column damper for reducing the seismic response of buildings. Issue 4 (14th September 2015) - Rozas, Luis; Boroschek, Ruben L.; Tamburrino, Aldo; Rojas, Matías
Summary: In this article, a new bidirectional tuned liquid column damper (BTLCD) is proposed for controlling the seismic response of structures. The device acts as two independent and orthogonal tuned liquid column dampers (TLCDs), but due to its configuration, it requires less liquid than two equivalent independent TLCDs. The equations of motion of the system formed by the BTLCD and the primary structure to be controlled are obtained by means of Lagrangian dynamics explicitly considering the non‐symetrical action of the damping forces. First, the primary structure was assumed to have two degrees of freedom (DOFs). Assuming that the system is excited by a base acceleration that can be considered to be a white noise random process, the optimum design parameters of the device were obtained to minimise the response of the primary structure. The optimum design parameters are presented as expressions covering a wide range of possible configurations for the device in a controlled structure. The use of a BTLCD to control the seismic response of several DOF structures was also studied, showing that if the structural response occurs mainly in two perpendicular modes, then the optimum design parameters for two DOF structures can be used. Experimental analyses of the BTLCD are developed in order to verify its dynamical properties. Finally, the device is designed for controlling the seismic response of a six DOF scale model. Numerical analyses are developed in order to verify the effectiveness and accuracy of the equations and design procedures proposed herein. Copyright © 2015 John Wiley & Sons, Ltd.